Four shades of black: Non-invasive scientific studies on the painted potteries from Shahr-i Sokhta, eastern Iran. (December 2018) - Eftekhari, Negar; Holakooei, Parviz; Sayyadshahri, Hamed; Vaccaro, Carmela
Abstract: Shahr-i Sokhta in east of Iran represents different stages of settlements from the fourth to the second millennium BC. A large assemblage of ceramics shards has been unearthed from Shahr-i Sokhta many of which are decorated with different shades of black, yellow and red colours. Micro X-ray fluorescence (μ-XRF) and micro-Raman spectroscopy (μ-Raman) on some seventy painted shards from Shahr-i Sokhta with polychrome, bi-chrome and monochrome decorations showed haematite and goethite as red and yellow decorations, respectively. Black decorations, however, consisted of four main groups including carbon black, magnetite, haematite and jacobsite. This paper represents a successful application of non-invasive spectroscopic methods for identifying pigments on archaeological ceramics. Highlights: Raman and XRF can be efficiently used for identifying archaeological pigments. Jacobsite can be found on ancient potteries as black pigment. Fe-based pigments are commonly found on archaeological painted potteries. Micro-Raman spectroscopy discriminated successfully different black pigments on ancient pottery.